Physical activity levels associated with insomnia and depressive symptoms in middle-aged and elderly patients with chronic schizophrenia - Liu, Zhiwei; Zhang, Yulong; Sun, Liang; Wang, Juan; Xia, Lei; Yang, Yating; Sun, Feng; Li, Wenzheng; Yao, Xianhu; Yang, Rongchun; Liu, Huanzhong (Frontiers in Psychiatry, 2023)
Background Previous evidence suggested that physical activity had beneficial effects on psychopathological symptoms, insomnia, or depressive symptoms in people with schizophrenia. This study investigated the association between physical activity levels and insomnia and depressive symptoms in middle-aged and elderly hospitalized patients with chronic schizophrenia (CS). Methods 179 participants were enrolled. We used the 30-item Positive and Negative Syndrome Scale (PANSS-30) to assess the psychopathological symptoms. We used Insomnia Severity Index scale (ISI) and 17-items Hamilton Depression Scale (HAMD-17) to evaluate insomnia and depressive symptoms. Daily physical activity time less than 30 minutes, within 30-60 minutes, and more than 60 minutes were defined as physical inactivity, moderate physical activity, and adequate physical activity, respectively. The data analysis was conducted using SPSS 23.0. Results The ISI total scores, HAMD total scores were still negatively correlated with physical activity levels. Logistic regression analysis revealed that older age, higher depressive factor scores and lower physical activity level were influential factors of insomnia symptoms in CS patients (P < 0.05). In addition, adequate physical activity (compared with physical inactivity) and higher negative and depressive factor scores were independently associated with depressive symptoms in CS patients (P < 0.05). Conclusion Physical activity levels were influential factors in comorbid insomnia and depressive symptoms in CS patients. Given the benefits of physical activity, it should be strengthened as a routine adjunct to clinical treatment or psychiatric care so as to improve the physical and mental health of patients with psychiatric symptoms.